Analysis of Online Learning Needs of Islamic Study Materials in The North Zone of Malaysia Polytechnics - Ahmad Fkrudin Mohamed Yusoff; Azmil Hashim; Norhisham Muhamad (Al-Hayat: Journal of Islamic Education, 2020)
This study was conducted with the purpose to identify the level of readiness and needs of the students towards the development of a mobile portal which applied problem-based learning for the Islamic Studies course in polytechnics. This study had implemented the method of survey and quantitative in nature. The number of 228 students who were enrolling the Islamic Studies course from five Malaysia polytechnics in the North Zone were selected randomly as sample. A set of questionnaires was used as research instrument. The data obtained were analysed descriptively using frequency, percentage and mean score in order to identify the level of readiness and needs of the students. The study found that students’ readiness level is very good, with 100% of the respondents owned mobile devices and 93.5% out of total respondents had experience in using the mobile devices for more than 3 years. The level of skill in using the mobile device also was good as all items had reached high level of mean score (3.82 – 4.14). Another criteria of readiness obtained from the data was students’ readiness towards problem-based learning strategy which all items had reached high level of mean score (3.94 – 4.20). Overall, the finding of this research showed that the level of students’ needs was high towards the development of this module as an effort to create an alternative pathway for the pedagogy of Islamic Studies.